Proximal versus distal adductor canal blocks for total knee arthroplasty: A protocol for randomized controlled trial. Issue 22 (29th May 2020) - Wang, Quan; Zhang, Yijun; Du, Jingyu; Lin, Xiangjin
Abstract: Background: Currently, there remains a paucity of literature about the efficiency of proximal adductor canal block (PACB) versus distal adductor canal block (DACB) for pain management after total knee arthroplasty (TKA). The purpose of this study is to perform a randomized controlled trial to compare the efficiency of PACB versus DACB for early postoperative pain treatment after TKA. Methods: This study is a 2-arm, parallel-group, randomized controlled trial that is conducted at a single university hospital in China. Subjects presenting for unilateral TKA are randomized in a 1:1 ratio to either a PACB or DACB group. The primary outcome of this noninferiority study is opioid consumption within the first 24 hours following surgery. Secondary outcomes include quadriceps strength, pain scores, distance ambulated, and patient satisfaction. Continuous variables are compared using Student t test. Results: This clinical trial is expected to provide evidence of whether the PACB and DACB provide similar analgesia after TKA. Trial registration: This study protocol was registered in Research Registry (researchregistry5440).